1996
DOI: 10.1128/mcb.16.3.762
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of G1 Cyclin-Dependent Kinase Activity during Growth Arrest of Human Breast Carcinoma Cells by Prostaglandin A2

Abstract: Prostaglandin A2 (PGA2) potently inhibits cell proliferation and suppresses tumor growth in vivo, but little is known regarding the molecular mechanisms mediating these effects. Here we demonstrate that treatment of breast carcinoma MCF-7 cells with PGA2 leads to G1 arrest associated with a dramatic decrease in the levels of cyclin D1 and cyclin-dependent kinase 4 (cdk4) and accompanied by an increase in the expression of p21. We further show that these effects occur independent of cellular p53 status. The dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 49 publications
(55 reference statements)
8
72
0
Order By: Relevance
“…This result is consistent with previous reports and support the notion that the inhibition of D-type cyclins may be the crucial event responsible for the antiproliferative action of numerous compounds, such as cyclic-AMP, prostaglandin A2 and alpha IFN (Gorospe et al, 1996;L'Allemain et al, 1997;Sewing et al, 1993;Tiefenbrun et al, 1996;Vadiveloo et al, 1996). The role of cyclin D3/ CDK4 in the cell cycle of 7TD1 cells is not clear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with previous reports and support the notion that the inhibition of D-type cyclins may be the crucial event responsible for the antiproliferative action of numerous compounds, such as cyclic-AMP, prostaglandin A2 and alpha IFN (Gorospe et al, 1996;L'Allemain et al, 1997;Sewing et al, 1993;Tiefenbrun et al, 1996;Vadiveloo et al, 1996). The role of cyclin D3/ CDK4 in the cell cycle of 7TD1 cells is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…Growth inhibition and cell cycle arrest in G 1 may be induced by a wide variety of factors such as TGFb (Florenes et al, 1996;Reynisdottir et al, 1995), nerve growth factor (Decker, 1995), alpha interferon (Tiefenbrun et al, 1996), ®brillar collagen (Koyoma et al, 1996), prostaglandin A2 (Gorospe et al, 1996), antiprogestin (Musgrove et al, 1997) or by antiproliferative agents such as cyclic-AMP , staurosporine (Schnier et al, 1996), lovastatin (Hengst et al, 1994). To date, the mechanisms underlying these antiproliferative e ects are a matter of great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A progressive loss of cyclin D1 expression was noted with increasing tRA concentration, approaching the limit of detection at 1 mM (Figure 1a). Cyclin D2 was undetectable in MCF-7 cell lysates, in agreement with previously published observations Gorospe et al, 1996). Re-probing of the Western blot with antibody to cyclin D3 revealed a similar trend (Figure 1b).…”
Section: Retinoid Treatment Of Human Breast Carcinoma Cell Lines Decrsupporting
confidence: 91%
“…For the inhibitors, p21 expression was also decreased by RAs, but was una ected by tamoxifen (Figure 7g). The p16 inhibitor is mutated and undetectable in MCF-7 cells (Gorospe et al, 1996, and data not shown). To determine if this complex series of changes in G 1 cell cycle proteins has functional consequences, assays for Cdk2 and Cdk4 activity were performed.…”
Section: Other Cyclin Complex Proteinsmentioning
confidence: 75%